2019
DOI: 10.1111/anu.12970
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of probiotics and influence on feed efficiency, growth parameters and reproductive performance in female rainbow trout (Oncorhynchus mykiss) broodstock

Abstract: The aim of this study was to determine the effects of dietary probiotics on reproductive performance, growth, haematological and biochemical parameters of female rainbow trout broodstock. A total of 60 broodstocks with an average initial weight of 2,267.4 ± 54.9 g were divided into four groups and three replicates in raceway ponds.Fish were fed with diets containing 0 (control), 1 × 10 9 (P1), 2 × 10 9 (P2) and 4 × 10 9 (P3) CFU probiotic per kg diet twice a day for 8 weeks before spawning season.Results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 81 publications
3
14
0
Order By: Relevance
“…The results showed that the feed intake was the same for all treatments, indicating that Bacillus NP5 supplementation in the feed did not affect its palatability (Tantikitti 2014). Similar results were observed in tilapia (Elsabagh et al 2018), juvenile olive flounder (Lee et al 2019), and rainbow trout (Nargesi et al 2019). Supplementation of 1.2-1.4% Bacillus.…”
Section: Discussionsupporting
confidence: 82%
“…The results showed that the feed intake was the same for all treatments, indicating that Bacillus NP5 supplementation in the feed did not affect its palatability (Tantikitti 2014). Similar results were observed in tilapia (Elsabagh et al 2018), juvenile olive flounder (Lee et al 2019), and rainbow trout (Nargesi et al 2019). Supplementation of 1.2-1.4% Bacillus.…”
Section: Discussionsupporting
confidence: 82%
“…Artificially cultured fishes are subjected in the hatchery to water quality and other parameters that can compromise the consistent production of healthy juveniles [ 148 ], although probiotic applications among broodstock, embryos and larvae have been studied inadequately. Female rainbow trout brood stock in raceway ponds supplemented with multi-probiotics before spawning season demonstrated production of eggs with higher diameters, increased fecundity, fertilization and hatching, yolk sac absorption, and eye development [ 14 ]. These results are consistent with beneficial responses to multiple-species LAB probiotic applications in the zebrafish hatchery, which led to consistent improvements in every measurable parameter of larval performance [ 149 ].…”
Section: Probiotics Application Under Farming Conditionmentioning
confidence: 99%
“…[ 13 ] for aquatic organisms as, “a probiotic organism can be regarded as a live, dead or component of a microbial cell, which can be administered via feed or into rearing water, benefiting the host by improving growth performance, feed utilization, immune health status, infectious disease resistance, and stress responses which is achieved at least in part via improving the microbial balance in hosts or ambient environment”. Probiotic research in the last decades has revealed positive effects on growth [ 14 , 15 ], digestive enzymes activities and feed utilization [ 16 ], immunity with upregulation of immune related genes [ 17 , 18 ], improvement of beneficial microbes in the gut and positive modification of intestinal structure [ 19 ], and disease protection [ 20 , 21 ], leading to an eco-friendly aquatic environmental management [ 22 ] in fish and shellfish farming.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have been reporting the relationship between biometric parameters and blood parameters of fishes to distinguish the healthy animals from disease-infected animals, and to evaluate the precise health status of the fish (Fazio et al, 2015;2017). Many authors have reported the influence of haematological parameters of fishes which depends on different types of feed (Dahiya et al, 2012;Nargesi et al, 2020;Ahmadifar et al 2020). However, very few reports are available related to the haematological indices and immune response of fish health (Ahmed et al 2020).…”
Section: Introductionmentioning
confidence: 99%